Legislative control over public enterprises : a study of legislative Committee in Public Undertakings, 1968-190 - Batra, Satish K. (Jaipur : Printwell, 1985)
This book examines legislative control over public enterprises in India. The present study concentrates on the legislative accountability of state enterprises and within broad spectrum consisting of questions debars and the legislative committee on public undertakings.
Includes bibliographical references and index
lje 17/01/2018
Loans
Keywords: Rajasthan (India). Legislative Assembly. Committee on Public Undertakings; Government business enterprises; Industrial policy; India